Salve a jurema sagrada! Identidades e direitos humanos na religiosidade afro-ameríndia em Campina Grande/PB - Farias, Camilo de Lélis Diniz de (2016)
This work has as its object the construction of cultural and political identity of Jurema Sagrada, a hibrid religious tradiction, that combines european, african and amerindian elements, in the urban space of Campina Grande, Paraíba. Methodologically, the research was based in bibliographical inquiry and etnography, where we sought, from observation and oral history, the construction of a religious and political experience narrative of the people of Jurema in Campina Grande, in opposition to their negative representation in religious, medical and juridical discourse. The work is also based in the subaltern studies perspective, intelectual school that proposes a political and epistemological inflection, aiming to elaboration of a critical theory of human rights from the persons and social groups historically marginalized, proposing the overcoming of the disjunctions of the modernity and the classical conceptions of human rights, that was deeply eurocentric and toward to legitimacy of capitalismo as economic and political system, and that failed in his intentions of universaliity, also criticized in this work. It analyzed also the effectiveness of the rights and public policies to the people of Jurema, where we conclude that the lacks of classic theoric approach of human rights reverberates also in you real application, being necessary, therefore, its reinvention based in experience of the subjects and social groups that citizenship was historicaly denied, for the construction of a effective universal pratice of human rights.